A 12-week randomized, double-blind, placebo-controlled multicenter study of choline-stabilized orthosilicic acid in patients with symptomatic knee osteoarthritis. Issue 1 (December 2017) - Geusens, Piet; Pavelka, Karel; Rovensky, Jozef; Vanhoof, Johan; Demeester, Nathalie; Calomme, Mario; Vanden Berghe, Dirk
Abstract Background The aim of this study was to assess the efficacy of choline-stabilized orthosilicic acid (ch-OSA) in patients with symptomatic knee osteoarthritis (OA). Methods In a multicenter, double-blind, placebo-controlled study, 211 patients with knee OA (Kellgren and Lawrence grade II or III) and moderate to moderately severe pain were randomly allocated to ch-OSA or placebo for 12 weeks. The primary outcome was the change in the WOMAC pain subscale from baseline to week 12. Secondary outcomes were changes from baseline to week 12 in WOMAC total, WOMAC stiffness, WOMAC physical function, Subject Global Assessment and levels of cartilage degradation biomarkers C-terminal telopeptide of collagen type II (CTX-II) and cartilage oligomeric matrix protein (COMP). Pre-specified subgroup analyses included the effect of gender. Results A total of 166 (120 women, 46 men) patients were included in the analysis (87 and 79 in the ch-OSA and placebo group, respectively). In the total study population, no differences were observed between the two treatment groups for the different outcomes but significant treatment x gender interactions were found. In men taking ch-OSA, a significant improvement in WOMAC total, WOMAC stiffness and WOMAC physical function as well as a lower increase in biomarker levels of cartilage degradation was observed, but not in women. The change in WOMAC pain showed a similar positive trend in men taking ch-OSA. Conclusion After 12 weeks of treatment, no effect was found of ch-OSA in the total study population on clinical parameters and biomarkers, but a gender interaction was observed. In men, ch-OSA was found effective in reducing symptoms of knee OA, which was associated with a slight but significant reduction of biomarkers that are related to cartilage degradation. Trial registration The study was registered retrospectively:ISRCTN88583133 . Registration date: 2015-10-07.